2014
DOI: 10.3389/fnhum.2014.00214
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a single night of sleep deprivation on fluency and prefrontal cortex function during divergent thinking

Abstract: The dorsal and ventral aspects of the prefrontal cortex (PFC) are the two regions most consistently recruited in divergent thinking tasks. Given that frontal tasks have been shown to be vulnerable to sleep loss, we explored the impact of a single night of sleep deprivation on fluency (i.e., number of generated responses) and PFC function during divergent thinking. Participants underwent functional magnetic resonance imaging scanning twice while engaged in the Alternate Uses Task (AUT) – once following a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 63 publications
1
20
1
Order By: Relevance
“…Cognitive problems in patients with insomnia or sleepdeprived individuals may be associated with low structural connectivity and structural abnormalities in the left thalamuspars triangularis tracts. It has been suggested that the neural networks of the cognitive system relate to decreased functional connectivity between the thalamus and inferior frontal gyrus in right-handed sleep-deprived individuals 15,46 or patients with insomnia. 10,14,18 Sleep-deprived adults showed reduced functional connectivity between the left inferior frontal gyrus and parahippocampal area in MRI scans during a selective attentional task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive problems in patients with insomnia or sleepdeprived individuals may be associated with low structural connectivity and structural abnormalities in the left thalamuspars triangularis tracts. It has been suggested that the neural networks of the cognitive system relate to decreased functional connectivity between the thalamus and inferior frontal gyrus in right-handed sleep-deprived individuals 15,46 or patients with insomnia. 10,14,18 Sleep-deprived adults showed reduced functional connectivity between the left inferior frontal gyrus and parahippocampal area in MRI scans during a selective attentional task.…”
Section: Discussionmentioning
confidence: 99%
“…13 Activity in the left pars triangularis of the inferior frontal gyrus decreased during category and letter fluency tests, 14 and the blood oxygen leveldependent signal in the left pars triangularis of the inferior frontal gyrus was more activated following short-term sleep deprivation when divergent thinking ability was needed. 15 A meta-analysis including studies comparing activation from rapid eye movement (REM) or NREM sleep to wakefulness found consistently decreased activation in the inferior frontal gyrus during REM sleep, and in the thalamus during NREM sleep. 16 Given the structural and functional abnormalities in the thalamus and left inferior frontal gyrus found in insomnia, investigating the neural connectivity between these 2 areas in insomnia is of interest.…”
Section: Introductionmentioning
confidence: 99%
“…DLPFC activation during creative task performance is thought to reflect the involvement of executive control processes (Beaty et al, 2016; Benedek et al, 2014a; Chen et al, 2015, in press). Another prefrontal region commonly implicated in neuroimaging studies of creative cognition is the left inferior frontal gyrus (IFG; Gonen-Yaacovi et al, 2013; Vartanian et al, 2014). The IFG shows robust activation during cognitive tasks that require controlled memory retrieval, particularly those requiring the selection of a target concept among a set of competing alternatives (Grindrod et al, 2008; Zhang et al, 2004).…”
Section: Neurocognitive Mechanisms Supporting Creative Idea Productionmentioning
confidence: 99%
“…Neuroimaging studies also have been conducted to assess the corresponding cerebral response and their relationship with behavioral changes in previous studies. In these studies, the frontal gyrus and parietal lobe showed more activation changes during the cognitive test, including working memory, verbal learning, thinking fluency, and attention test [12,15,45,46]. Except for these two brain regions, studies, which used resting state fMRI, also showed decreased ALFF in the precuneus, angular gyrus, and thalamus [11,32,43].…”
Section: Working Memory and Alff Changes After Sdmentioning
confidence: 99%